Hubungan Gaya kepemimpinan Transformasional, Komitmen Organisasional dengan Kinerja Pustakawan - Setiawan Setiawan; Kifayah Amar (Pascasarjana UM, 2016)
Abstract: The aims of this study are (1) to examine the relationship of transformational leadership style and organizational commitment. (2) to examine the relationship of transformational leadership style and the performance of librarians at the library of State University of Malang. (3) to examine the relationship of organizational commitment to the performance of librarians at the library of State University of Malang. This is a quantitative research with correlation research design and ex post facto method approach. Variable in this study consists of independent variables (X1) which is Transformational leadership style, (X2) which is Organizational Commitment and dependent variable (Y) which is the librarian performance. The data collection method uses questionnaires, observation and documentation. The research instrument is tested on its validity and reliability. The method of data analysis is multiple regressions. The results of the research reveal that (1) there is correlation or a positive and significant relationship between Transformational Leadership Style and Organizational Commitment in the Library of the State University of Malang. (2) there is a significant relationship between Transformational Leadership Style with Librarian Performance at the library of State University of Malang. (3) there is a significant relationship of Organizational Commitment to the librarian Performance at the library of State University of Malang.Key Words: transformational leadership style, organizational commitment, librarian performance Abstrak: Tujuan dari penelitian ini adalah. (1) Untuk mengetahui hubungan antara gaya kepemimpinan transformasional dengan komitmen organisasional.(2) Untuk mengetahui hubungan antara gaya kepemimpinan transformasional dengan kinerja pustakawan di Perpustakaan Universitas Negeri Malang. (3). Untuk mengetahui hubungan antara komitmen organisasional dengan kinerja pustakawan di perpustakaan universitas Negeri Malang. Jenis Penelitian ini adalah penelitian kuantitatif dengan rancangan penelitian korelasional dengan pendekatan metode ex post facto”.Variable dalam penelitian ini terdiri dari variable bebas (X1) yaitu Gaya kepemimpinan Transformational. (X2) Komitmen Organisasional. Dan variable terikat (Y) yaitu Kinerja Pustakawan.Metode Pengumpulan data dengan kuisioner, observasi dan dokumentasi.Pengujian instrumen penelitian dengan validitas, reabilitas.Metode analisa data dengan Analisis regresi berganda. Hasil Penelitian yaitu (1).Terdapat korelasi atau hubungan positif dan signifikan antara Gaya Kepemimpinan Transformasional dengan Komitmen Organisational di Perpustakaan Universitas Negeri Malang.(2)Terdapat hubungan yang signifikan antara Gaya Kepemimpinan Transformational dengan Kinerja Pustakawan di Perpustakaan Universitas Negeri Malang. (3) Terdapat hubungan yang signifikan antara Komitmen Organisational dengan Kinerja Pustakawan di Perpustakaan Universitas Negeri Malang.Kata Kunci : gaya kepemimpinan transformasional, komitmen organisasional, kinerja pustakawan